PENGARUH FINANCIAL DISTRESS DAN LEVERAGE TERHADAP AUDIT DELAY DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI - Hari Stiawan; Fitria Eka Ningsih (Pusat Riset dan Inovasi Nasional, 2021)
Audit delay is the length of time for the completion of an audit of a company's financial statements measured from the closing date of the book year to the date of issuance of financial statements. This study aims to analyze the effect of financial distress and leverage on audit delay. In addition, this study also uses company size as a moderating variable, which aims to determine the role of company size in the relationship between financial distress and leverage on audit delay. This research was conducted at the Indonesia Stock Exchange (IDX) through the investment gallery especially in the banking sector in Indonesia in 2014-2018. This study uses secondary data in the form of financial statements of banking companies in 2014-2018. The research sample is quantitative and uses purposive sampling method, with a total sample of 130 samples. The research methodology used is multiple linear regression and Moderated Regression Analysis (MRA) using SPSS version 24. The results of this study are that financial distress has a significant effect on audit delay, leverage has a significant effect on audit delay in the banking sector in the Indonesia Stock Exchange (BEI) year 2014-2018. And company size strengthens the relationship between financial distress and leverage on audit delay in the banking sector on the Indonesia Stock Exchange (IDX) in 2014-2018.